GAS Political public space in the satire theatre case study on the performance eyayu fenges” Ethiopian satire theater: political public space in the satire theatre case study on the performance eyayu fenges” Ethiopian satire theater (International Journal of Scientific Research and Management (IJSRM), 2019)
Abstract፡ This article aims to describe about the techniques of make understanding for the space of audience or target group in the satire drama in the stage. The researcher would watch the theater in YouTube and in the stage and also read the script which written by Bereket Belayneh in the type of satire drama, its function in terms of political and social issues. In the addition to the above mentioned these script and play must show the use of satire for political and social criticism for the audience clearly with easy understanding. The other thing that plays show transmitted of the message to the higher officials in the comic entertaining way to the audience of the satire drama. Besides techniques, purpose and different features of satire has investigated from the relevant references. Its researcher mainly has shown the technique of making understand for the audience that have been watched the satire theater on the stage. Bereket Belayneh and Girum Zenebe Eyayu fenges Ethiopian Satire Theater focusing on political satire to find the satire and comic elements used in the humor in order to ridicule the political evils and suggest solutions with in artistically color. The primary sources of this article are Bereket Belayneh and Girum zenebe Eyayu fenges Ethiopian Satire Theater. It’s have used as methodology a qualitative descriptive analysis and have use the document study which is that in library, research digital media sites and the relative relevant materials.